1999
DOI: 10.1046/j.1525-1438.1999.99007.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection and cervical intraepithelial neoplasia

Abstract: The impact of sexually transmitted diseases (STDs) on the development of cervical intraepithelial neoplasia (CIN) has been increasingly recognized over the last 20 years. Much attention has been focused on human papillomavirus (HPV) and the potential for screening for certain HPV types alongside standard cervical cytology in the hope of identifying those females at particular risk of developing high grade CIN or invasive carcinoma. Some infections, for example herpes simplex virus (HSV), have been heavily inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 82 publications
2
17
0
1
Order By: Relevance
“…CT infection has been shown to be more frequent in women with CIN than in women with normal cytology (5,15). Other studies however do not support a relationship between CT and CIN or abnormal cervical cytology (16,17). Chlamydial cervicitis has been suspected to be a risk factor for SIL (Squamous intraepithelial neoplasia) and cervical cancer on the basis of case control comparisons of serological tests but after adjusting for HPV (Human Papilloma virus) infection, the risk of cervical cancer associated with chlamydial seropositivity was considered low (OR=2) (18).…”
Section: Discussionmentioning
confidence: 98%
“…CT infection has been shown to be more frequent in women with CIN than in women with normal cytology (5,15). Other studies however do not support a relationship between CT and CIN or abnormal cervical cytology (16,17). Chlamydial cervicitis has been suspected to be a risk factor for SIL (Squamous intraepithelial neoplasia) and cervical cancer on the basis of case control comparisons of serological tests but after adjusting for HPV (Human Papilloma virus) infection, the risk of cervical cancer associated with chlamydial seropositivity was considered low (OR=2) (18).…”
Section: Discussionmentioning
confidence: 98%
“…18,19 Earlier studies have found a significantly higher prevalence of Ct-DNA among HPV-positive women than HPV-negative ones 2,[20][21][22] as well as evidence that Ct is an HPV cofactor in the etiology of displastic and neoplastic cervical abnormalities and CC. [23][24][25] Cervical Ct infection has been clinically documented to be associated with cytological atypia and cervical metaplasia, thus damaging epithelial integrity, allowing the HPV access to the basal epithelium and increasing viral load.…”
Section: Chlamydia Trachomatis Prevalence and Chlamydial/ Hpv Co-infementioning
confidence: 99%
“…A local deficit of immunity during the reparative phase of the epithelial surface under inflammatory conditions may make cervical epithelial cells more susceptible to other pathogens. 18,19 On the other hand, it has been also suggested that the association between Ct and HPV lies only in their shared route of transmission, as both pathogens are markers of sexual risk behaviors. 25 Our previous study 26 revealed an overall HPV prevalence of 18.2% among unvaccinated young females with normal cytological findings and a particularly high prevalence (10.1%) of highrisk HPV genotypes, underlining the need to optimize preventive measures against STIs among healthy young females.…”
Section: Chlamydia Trachomatis Prevalence and Chlamydial/ Hpv Co-infementioning
confidence: 99%
“…A partir de fines los años 60 y comienzos de los 70 los estudios epidemiológicos han proveído abundante información que sugería que el cáncer cérvico-uterino se transmitía a través de la actividad coital, poniendo énfasis en un posible agente infeccioso como relevante en la etiología de la enfermedad. Inicialmente la evidencia apuntó al Virus Herpes Simple, se han involucrado también a la Neisseria, Clamydia, Citomegalovirus, Tricomonas y otros agentes infecciosos; sin embargo desde el inicio de los 80 la atención gradualmente se fue enfocando en un nuevo candidato, el virus papiloma humano, basado en la rápida evidencia acumulada a través de estudios epidemiológicos, clínicos y de biología molecular (11,12). La asociación es independiente de la población estudiada, del mé-todo de detección viral utilizado y satisface todos los criterios de causalidad comúnmente empleados (consistencia, temporalidad, coherencia y evidencia experimental) (8,13,14,15).…”
Section: Rol Del Virus Papiloma Humano (Vph)unclassified